INTEGRAL QUALITY OF MANAGEMENT AND ANALYSIS OF MANAGERIAL DECISION-MAKING BASED ON THE BEHAVIORAL APPROACH - Lomachynska, Iryna; Skoruk, Alina; Liventsov, Roman; Suprunenko, Maria (Current Problems of Sustainable Development, 2026)
The shift in emphasis from rational aspects of managerial decision-making to bounded rationality and irrationality, as well as the gap between existing theoretical concepts and real processes of their adoption, necessitate the search for new approaches to improving the organizational management model. In this context, the analysis of managerial decision-making based on the application of a behavioral approach is an integral part of management professionalization. At the same time, the behavioral approach is a tool, and management professionalization is the process of implementing these tools for the purpose of revealing and developing intellectual capital. The purpose of the study is the theoretical and methodological justification and practical application of the analysis of the organizational management model based on the integration of the behavioral approach and its relationship with the integral quality of management. The materials of the study are: scientific works by Ukrainian and international authors, as well as regulatory and analytical Data-driven management on the activities of specific business entities. To clarify the conceptual apparatus, the relationship between the basic categories, the system method was used, as well as the methods of logical generalization and theoretical modeling. To analyze the contradictions, dialectical, abstract-logical and comparative methods were used. Thanks to behavioral analysis, in particular, based on the Delphi method, the management model of the Kernel company was analyzed. The methods of abstraction and modeling, system analysis allowed us to make theoretical and applied generalizations, to substantiate the directions of improving the quality of management decisions in the context of management professionalization. Analysis of management decision-making based on the application of a behavioral approach is an integral part of management professionalization. This is due to the following: the behavioral approach allows us to expand the scientific base in the context of how people perceive information; allows us to recognize irrational deviations in thinking and decision-making; ensures the implementation of the management process not on the basis of emotions, intuition, chaos, but focusing on the systemic awareness of the process, which is based on intellectual tools and psychological stability; the behavioral approach turns intuition into an analytical tool that allows you to measure and predict human capital. Management professionalization is defined not so much by the mastery of decision-making tools as by the ability to identify “behavioral traps” in conditions of uncertainty, to demonstrate the adaptability of its behavior model in conditions of nonlinear development of the organization, the ability to adjust group dynamics and ensure the emotional stability of the team and motivate it, which in general determines the growth of the integral quality of management as a whole. As a result, adaptation to change, openness to innovation, the implementation of international management standards and investment in professional development of personnel are critically important factors for ensuring the growth of the efficiency and competitiveness of a business organization. In further scientific research, it is proposed to focus on the use of digital tools to take into account behavioral aspects when making management decisions. Promising areas that require further development and implementation are AI-based decision support, Data-driven management, and automation of behavioral auditing, which will generally increase the level of disciplined behavior of the manager.
Keywords: professionalization of management; integral quality of management; behavioral approach; digital transformation; management model; adaptive training of management personnel; human potential; intellectual capital; motivational values; digitalization; socio-cultural context; bifurcation; innovative development